The Western Sahara question and international law : recognition doctrine and self-determination - Allen, Steve, 1968-; Trinidad, Jamie (Routledge, 2024)
"This book analyses recent developments concerning the application of the international legal doctrines of recognition and self-determination in relation to the Western Sahara Question. It investigates the emergent shift in favour of Morocco's sovereignty claim to Western Sahara as apparent from the positions adopted by an increasing number of third States in the United Nations and the recent spate of third States establishing consulates in Western Sahara, with Morocco's encouragement. It reflects on what the functioning of the doctrines of recognition and self-determination in this situation reveals about contemporary international law in practice more generally. The work will be of interest to scholars, researchers, and postgraduate students as well as practitioners of public international law who have a particular interest in decolonisation, self-determination disputes and/or conflicts about natural resource entitlements. It will also appeal to readers with an interest in the work of International Organisations, including the United Nations, the European Union, and the African Union, and to specialists in international relations and regional politics"-- Provided by publisher.
"Routledge focus"-- cover.
Keywords: Self-determination, National -- Western Sahara.; Recognition (International law); Sovereignty.; Western Sahara -- International status.; Western Sahara -- Relations -- Morocco.; Morocco -- Relations -- Western Sahara.; Droit des peuples à disposer d'eux-mêmes -- Sahara occidental.; Reconnaissance (Droit international); Souveraineté.; sovereignty.; International law; International relations; Self-determination, National; Sovereignty; Morocco; Western Sahara; LAW / International; LAW / Jurisprudence; Electronic books.